Vortex-mediated relaxation of magnon BEC into light Higgs quasiparticles - Autti, S; Heikkinen, P J; Laine, S M; Mäkinen, J T; Thuneberg, E V; Zavjalov, V V; Eltsov, V B (arXiv.org, 2021)
A magnon Bose-Einstein condensate in superfluid \(^3\)He is a fine instrument for studying the surrounding macroscopic quantum system. At zero temperature, the BEC is subject to a few, distinct forms of decay into other collective excitations, owing to momentum and energy conservation in a quantum vacuum. We study the vortex-Higgs mechanism: the vortices relax the requirement for momentum conservation, allowing the optical magnons of the BEC to transform into light Higgs quasiparticles. This observation expands the spectrum of possible interactions between magnetic quasiparticles in \(^3\)He-B, opens pathways for hunting down elusive phenomena such as the Kelvin wave cascade or bound Majorana fermions, and lays groundwork for building magnon-based quantum devices.